Preimplantation factor modulates trophoblastic invasion throughout the decidualization of human endometrial stromal cells - Esther Dos Santos; Hadia Moindjie; Valérie Sérazin; Lucie Arnould; Yoann Rodriguez; Khadija Fathallah; Eytan R. Barnea; François Vialard; Marie-Noëlle Dieudonné (BMC, 2021)
Abstract Background Successful human embryo implantation requires the differentiation of endometrial stromal cells (ESCs) into decidual cells during a process called decidualization. ESCs express specific markers of decidualization, including prolactin, insulin-like growth factor-binding protein-1 (IGFBP-1), and connexin-43. Decidual cells also control of trophoblast invasion by secreting various factors, such as matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases. Preimplantation factor (PIF) is a recently identified, embryo-derived peptide with activities at the fetal-maternal interface. It creates a favorable pro-inflammatory environment in human endometrium and directly controls placental development by increasing the human trophoblastic cells' ability to invade the endometrium. We hypothesized that PIF's effects on the endometrium counteract its pro-invasive effects. Methods We tested sPIF effect on the expression of three decidualization markers by RT-qPCR and/or immunochemiluminescence assay. We examined sPIF effect on human ESC migration by performing an in vitro wound healing assay. We analyzed sPIF effect on endometrial control of human trophoblast invasion by performing a zymography and an invasion assay. Results Firstly, we found that a synthetic analog of PIF (sPIF) significantly upregulates the mRNA expression of IGFBP-1 and connexin-43, and prolactin secretion in ESCs - suggesting a pro-differentiation effect. Secondly, we showed that the HTR-8/SVneo trophoblastic cell line's invasive ability was low in the presence of conditioned media from ESCs cultured with sPIF. Thirdly, this PIF's anti-invasive action was associated with a specifically decrease in MMP-9 activity. Conclusion Taken as a whole, our results suggest that PIF accentuates the decidualization process and the production of endometrial factors that limit trophoblast invasion. By controlling both trophoblast and endometrial cells, PIF therefore appears to be a pivotal player in the human embryo implantation process.